Analisis Yuridis Normatif Praktik Investasi Ilegal Pada Aplikasi Binomo - Nadila Sandra; Komariah Komariah; Yohana Puspitasari Wardoyo (Universitas Muhammadiyah Malang, 2022)
Currently, there are many types of investment and trading in Indonesia, one of which is the Binomo application. The public does not know whether the Binomo application is included in the legal or illegal investment category, and the public does not know what happens if a loss occurs. The problems raised by the author are to determine investments based on the perspective of civil law and determine the factors that cause people to be interested in illegal investment applications. The research method uses normative juridical, using library research, among others, researching favorable legal provisions and legal principles, books, or other documents related to the research being researched. Based on the research results, the Binomo application is part of the platform that provides securities transaction services and financial assets that do not have permission from the OJK and Bappeti, and binary options such as Bonomo are gambling. Some factors that make people tempted by this are low literacy, economic difficulties, and the number of people trapped by testimonials from people who have joined first. The public needs awareness regarding literacy that discusses investments from the government, Bappeti, and OJK, which are legal in Indonesia. Clear regulations are needed regarding applications from the Play Store, which should explain the details of the application, both from regulations and the system run by the application.